2017
DOI: 10.1167/iovs.17-21734
|View full text |Cite
|
Sign up to set email alerts
|

Joint Analysis of Nuclear and Mitochondrial Variants in Age-Related Macular Degeneration Identifies Novel Loci TRPM1 and ABHD2/RLBP1

Abstract: PurposePresently, 52 independent nuclear single nucleotide polymorphisms (nSNPs) have been associated with age-related macular degeneration (AMD) but their effects do not explain all its variance. Genetic interactions between the nuclear and mitochondrial (mt) genome may unearth additional genetic loci previously unassociated with AMD risk.MethodsJoint effects of nSNPs and selected mtSNPs were analyzed by two degree of freedom (2df) joint tests of association in the International AMD Genomics Consortium (IAMDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…A similar effect was observed when mtDNA mutation m.12771G>A (gene MT-ND5 ) was combined with polymorphisms of nuclear DNA rs4932478, rs4932480, rs11459118, rs875390, rs875391, rs2351006, rs144871045 and rs2070780 (loci ABHD2 / RLBP1 , chromosome 15). 104 In the research work by Meng et al, 105 it was shown that the combination of the nuclear modifier allele A10S in the TRMU gene with mitochondrial genome mutation m.1555A>G ( MT-RNR1 gene) increased the risk of deafness.…”
Section: Relationship Between Nuclear Dna and Mtdna In Mitochondrial mentioning
confidence: 99%
“…A similar effect was observed when mtDNA mutation m.12771G>A (gene MT-ND5 ) was combined with polymorphisms of nuclear DNA rs4932478, rs4932480, rs11459118, rs875390, rs875391, rs2351006, rs144871045 and rs2070780 (loci ABHD2 / RLBP1 , chromosome 15). 104 In the research work by Meng et al, 105 it was shown that the combination of the nuclear modifier allele A10S in the TRMU gene with mitochondrial genome mutation m.1555A>G ( MT-RNR1 gene) increased the risk of deafness.…”
Section: Relationship Between Nuclear Dna and Mtdna In Mitochondrial mentioning
confidence: 99%
“…It was found to participate in generating depolarising light response and to functionally regulate melanocyte pigmentation 22,23 . TRPM1 genetic polymorphisms had been implicated in human diseases, including CSNB1, age‐related macular degeneration, albuminuria and mental disorder like schizophrenia and autism 13,24‐28 . Notably, production of anti‐TRPM1 autoantibodies resulted in melanoma‐associated retinopathy (MAR), an autoimmune syndrome presented with photophobia, photopsia and enhanced perception, which were similar to those described in VVAE 29,30 .…”
Section: Discussionmentioning
confidence: 55%
“…While 27 of the 29 loci overlap with regions that were identified in the previous screen for AMD (using the identical data set) [ 13 ], two additional AMD loci were identified in this study by accounting for age differences. One hit is located in a novel AMD region on chromosome 18 (rs9973159, P Agejoint = 3.91 x 10 −8 ) and one in a region on chromosome 15 that was recently identified for AMD in a joint analysis of nuclear and mitochondrial variants [ 20 ] (rs2070780, P Agejoint = 3.19 x 10 −8 , Figs 2 and 3 , Table 2 , S3 Table ). A search for independent second signals at the two loci by conditioning on the two lead variants did not reveal any independent second signals (P Agejoin;cond ≥ 5 x 10 −8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, by accounting for potentially differential genetic effects between age groups, we identified two AMD loci that were undetected in a previous main effect screen using the identical dataset [ 13 ]. These two additional AMD loci point to a novel AMD GWAS region on chromosome 15 and one region on chromosome 18 that was recently identified as AMD risk locus in a joint analysis of nuclear and mitochondrial variants [ 20 ]. Thirdly, we found no differences in the genetic effects for late AMD between men and women despite considerable power in our study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation